Bentonite-concrete mix for ufer grounding - Siow, Chun Lim (2014)
Based on the literature, Bentonite is one of the most efficient grounding improvement material. There are two commercially available types of Bentonite namely Sodium and Calcium Bentonite. However, previous studies have not considered the effect of type of Bentonite on its performance as grounding improvement material. In addition, there were insufficient information of Bentonite which is imperative to explain the effectiveness of Bentonite as grounding improvement material. Based on a series of experimental and theoretical work, both types of Bentonite were characterized and it was found that Sodium Bentonite was better due to its superior moisture absorption and retention capability, swelling capacity under hydrated condition as well as its significantly lower resistivity. Furthermore, the behaviour of backfill materials especially Bentonite under the application of high voltage which could be due to lightning and power system fault events was not studied extensively in the literature. Hence further characterisation of Sodium Bentonite with respect to its high voltage response which includes transient and high alternating voltage was done. Indeed the performance of Sodium Bentonite was found to be superior compared to other selected backfill materials such as sand and cement judging on its lower 50% impulse breakdown voltage as well as alternating breakdown voltage. These information together with the results of statistical studies done on the voltage at breakdown and time to breakdown of Bentonite were not available in the literature. On the other hand, Ufer grounding is an effective grounding practice provided that moisture is present. This is because concrete is the main component of Ufer grounding and previous studies have concluded that concrete exhibits significantly higher resistivity when the moisture content is low. The good properties of Bentonite as grounding improvement material as aforementioned may be able to improve the electrical properties of concrete which in turn will result in an improvement of Ufer grounding. Therefore, introduction of Bentonite into concrete mix of Ufer grounding at 0-70% proportions by volume was done at a site with soil resistivity of 121Ωm and its steady state ground resistance performance was investigated by adopting the Fall of Potential measurement method. After one year of measurement of low frequency ground resistance of Bentonite mixed concrete encased steel cage, 30% Bentonite-concrete mix was found to be the best mix which yield the lowest average ground resistance with the least fluctuation as well. The best mix was found to be about 13% better than the standard concrete mix in terms of ground resistance. Therefore, the behaviour of the best mix was investigated at another site with soil of much higher resistivity at 1672Ωm. Sodium Bentonite was used instead of Calcium Bentonite henceforth due to its superior characteristics and the optimum mixing ration remains at 30% base on the resistivity variation of both type of Bentonite. After six months of monitoring, it was found that the performance of best mix was again superior compared to several other systems which include bentonite slurry, background soil and driven copper rod by judging on the ground resistance as well as cost factor. Hence it can be concluded that the best mix could be a good grounding improvement material which can also be used as fencing‟s foundation as the mechanical strength was not greatly reduced. In the final phase of this research, the best mix together with the standard concrete mix were installed in five sites with various soil resistivity to determine the correlation between ground resistance and the localized soil resistivity. Standard concrete mix was used as well due to its relatively good performance compared to other ratios of Bentonite-concrete mix except for 30%. These correlations would allow prediction of ground resistance of the best mix and standard concrete mix at a given soil resistivity and thus serves as a guide for future applications by engineers in designing grounding system using the best mix. Finally it was found that by comparing their respective correlations, the best mix is 16% better than the standard concrete mix. This difference is significant especially at sites with high soil resistivity.